An observational cross-sectional study of the role of transformational leadership style in reducing the risk of nosocomial infections - Ariyanti, Rasid; Nugroho, Sri Hananto Ponco; Widiyanto, Puguh (Innovation in Health for Society, 2026)
Nosocomial infections remain a serious challenge in healthcare services, contributing significantly to morbidity and mortality. This study aims to analyze the relationship between transformational leadership style and the reduction of nosocomial infection risk in the inpatient ward of the Hospital. A quantitative research method with a cross-sectional design was employed. Data were collected using questionnaires that measured nurses’ perceptions of leadership style and actions to reduce nosocomial infection risk, and were analyzed using the Spearman Rank test. The results revealed a significant positive relationship between transformational leadership style and infection risk reduction measures (p<0.05). These findings emphasize the critical importance of leadership in enhancing patient safety. Keywords: Healthcare system, innovation in leadership, nosocomial infection, nursing management, transformational leadership